Welfare investigations in farmed lumpfish (Cyclopterus lumpus L.) used for sea lice control in the salmon industry - CAROLINA RABADAN (2022)
Lumpfish (Cyclopterus lumpus L.) are commercially important species used world-wide since 2008 as cleaner fish to control sea lice (Lepeophtheirus salmonis), one of the most significant parasites affecting Atlantic salmon (Salmo salar L.) and costing the industry over 500M € annually. However, lumpfish mortalities in sea cages can be as high as 100%, raising welfare concerns on whether their use continue to be acceptable. The industry is under scrutiny by both government agencies and non-governmental organisations to improve lumpfish welfare, but they do not provide much direction as welfare standards are not developed yet for this species. This thesis examined novel ways to monitor welfare in farmed lumpfish in order to increase the sustainability and ethical use of lumpfish in aquaculture. Chapter 1 reviewed the bases of fish welfare as well as lumpfish biology, use as cleaner fish and main challenges within the aquaculture industry. Chapter 2 developed and tested a practical, easy-to-use, validated and highly repeatable (ICC=0.83) scoring index combining six Operational Welfare Indicators to measure lumpfish welfare under farm conditions. Chapter 3 found welfare deterioration in sea cages to be dependent on time spent at sea and to be worse in smaller fish. Welfare monitoring should be particularly regular during the first months post-transfer at sea. Chapter 4 found differences in welfare, growth, feeding preferences and gut microbiota between different genetic stocks of lumpfish, with Icelandic lumpfish growing faster, showing better welfare and ingesting more formulated pellets than Scottish lumpfish. Significant associations in the gut microbiota were identified between compromised welfare and Candidatus branchiomonas and high plasma cortisol and Clostridium, suggesting these could be used as potential biomarkers. Chapter 5 investigated the effect of sea lice ingestion in lumpfish welfare and gut health and found that sea lice ingestion did not have any influence and is not detrimental for lumpfish welfare. Welfare investigations under commercial conditions proved that lumpfish welfare status (measured by using individual morphological indicators) deteriorates in time when stocked in salmon net pens, resulting in an increase of these scores, which also differ between commercial sites and populations under the same conditions. The ability of monitoring welfare in regular basis serves as an early warning for health and welfare issues and the application of the index along the knowledge withdrawn from this thesis will help farmers to identify critical periods where lumpfish welfare starts deteriorating, as well as provide scientific reference to policy developers, welfare organisations and NGOs and quality assurance schemes. In this sense, welfare standards for these novel species can be developed, and corrective actions can be taken before any issues progress into mortalities. This will enhance the sustainability of the lumpfish industry and will reduce economic costs of sea lice management, mitigating environmental impacts for not using chemotherapeutants at sea and improving salmon welfare overall.